VD_FINDINFO 14/2016 vom 18. Dezember 2014 - VD Tribunal cantonal (2014)
RÉCUSATION, REJET DE LA DEMANDE | 47 al. 1 let. a CPC (CH), 47 al. 1 let. b CPC (CH), 47 al. 1 let. f CPC (CH), 47 CPC (CH), 8a al. 3 CDPJ, 8a CDPJ